A Tyrosine Motif in the Cytoplasmic Domain of Mason-Pfizer Monkey Virus Is Essential for the Incorporation of Glycoprotein into Virions - Song, Chisu (American Society for Microbiology, 2003)
Mason-Pfizer monkey virus (M-PMV) encodes a transmembrane (TM) glycoprotein with a 38-amino-acid-long cytoplasmic domain. After the release of the immature virus, a viral protease-mediated cleavage occurs within the cytoplasmic domain, resulting in the loss of 17 amino acids from the carboxy terminus. This maturational cleavage occurs between a histidine at position 21 and a tyrosine at position 22 in the cytoplasmic domain of the TM protein. We have demonstrated previously that a truncated TM glycoprotein with a 21-amino-acid-long cytoplasmic tail showed enhanced fusogenicity but could not be incorporated into virions. These results suggest that postassembly cleavage of the cytoplasmic domain removes a necessary incorporation signal and activates fusion activity. To investigate the contribution of tyrosine residues to the function of the glycoprotein complex and virus replication, we have introduced amino acid substitutions into two tyrosine residues found in the cytoplasmic domain. The effects of these mutations on glycoprotein biosynthesis and function, as well as on virus infectivity, have been examined. Mutation of tyrosine 34 to alanine had little effect on glycoprotein function. In contrast, substitutions at tyrosine 22 modulated fusion activity in either a positive or negative manner, depending on the substituting amino acid. Moreover, any nonaromatic substitution at this position blocked glycoprotein incorporation into virions and abolished infectivity. These results demonstrate that M-PMV employs a tyrosine signal for the selective incorporation of glycoprotein into budding virions. Antibody uptake studies show that tyrosine 22 is part of an efficient internalization signal in the cytoplasmic domain of the M-PMV glycoprotein that can also be positively and negatively influenced by changes at this site.